Social-Emotional Concepts in Nana Asma'u's Thought and Their Relevance to Islamic Religious Education - Maulidah, Sakhat; Subhi, Muhamad Rifa’i; Anekasari, Rahmi (The Future of Education Journal, 2025)
This research aims to analyze the social-emotional concept in Nana Asma'u's thought and its relevance to Islamic Religious Education. This research is classified as library research with a qualitative approach. The data sources used are derived from journal articles. The data collection technique involves understanding and studying theories from various relevant literature and library materials. The data analysis technique in this research is conducted qualitatively through three stages: the data condensation stage where researchers perform filtering, selection, and focusing of data to make it easier to understand and process according to the research focus, followed by the data display stage, and the conclusion drawing and verification stage. The results of this research show that Nana Asma'u's social-emotional approach offers much-needed solutions in modern education, which focuses on the balance between cognitive, emotional, and social aspects in character formation of students. By prioritizing love, empathy, social responsibility, and women's empowerment. Through the Yan Taru method, Nana Asma'u successfully created an educational system that emphasizes non-dehumanizing human relationships. The novelty of this research lies in strengthening the social-emotional aspects in Islamic Religious Education through a historical-conceptual approach from a classical Muslim female figure, which has rarely been discussed specifically in the context of contemporary education. Moreover, this research highlights the significant contribution of the female figure Nana Asma'u in integrating spiritual, social, and emotional values in Islamic education that is inclusive, humanistic, and relevant to contemporary needs. Keywords: Islamic Religious Education, Nana Asma'u, Nana Asma'u's Thought, Social-Emotional, Women's Education Pioneer.